Shared Inuit Culture: European Museums and Arctic Communities - Buijs, Cunera (Études Inuit Studies, 2018)
Since the 1980s, museum professionals have increasingly committed to sharing collections with the descendants of people and communities from whom the collected artifacts originated. As late as the 1970s, Indigenous people were not considered stakeholders in the collection and exhibition of their own cultural artifacts. Recently, however, exemplary cases of collection sharing have occurred in North American and European museums. Museums have become “contact zones” as issues of decolonization have come to the fore. This article discusses the sharing of material culture and “double” position of anthropological museums, rooted in their own (colonial) history but in possession of another’s culture. Ownership issues, access, and ethics are important for local communities but not always easy for museums to negotiate. This article describes thirteen examples of collaborative partnerships between museums, for the most part large, urban, European, postcolonial institutions, and Arctic Indigenous communities. I argue that open communication, collection research, and an increasing level of co-curation are prerequisites for changes in museum practice, and these changes will benefit both the institutions and the communities involved.